Association of circulating adipokines with metabolic dyslipidemia in obese versus non-obese individuals. Issue 1 (January 2016) - Rahimlou, Mehran; Mirzaei, Khadijeh; Keshavarz, Seyed Ali; Hossein-nezhad, Arash
Abstract: Aim: Previous studies have shown that circulating adipokines may play an important role in the pathogenesis of some obesity related chronic disease such as dyslipidemia and type2 diabetes mellitus. The aim of the present study was to investigate the association between vaspin, omentin-1 and retinol binding protein-4 levels with metabolic dyslipidemia (MD) criteria in obese and non-obese individuals. Method: The study was conducted on 170 obese and 81 non-obese individuals. After collecting the blood samples, serum levels metabolic parameters as well as three circulating adipokines and body composition were measured. Results: No significant difference was noted regarding the mean serum levels of omentin-1 and vaspin between the obese and non-obese groups, while, serum level of RBP4 was significantly higher in the non-obese group. We found the 0.22 increased risk of MD in obese individuals with higher RBP4 concentration. After the adjustment for confounding factors, this association was still significant. No significant association was noted between MD and its components relative risks with omentin-1 and vaspin levels. Conclusion: Our study demonstrated that circulating RBP4 was significantly higher in the obese individuals which may increase the risk of MD in them. Further researches are needed to address this association.